Promoting Storytelling in Enhancing Health Vocational Students’ Speaking Achievement - Istanto, Wisnu; Candra, Diah Arumita; Heryani, Heni (Anglophile Journal, 2021)
Soft skills development requires the use of education media and forums. While storytelling may be used in competitions, media classes do not use it as a teaching media. Storytelling in the classroom hasn't been used to its fullest potential. English language proficiency can be improved through the use of digital storytelling, specifically on YouTube, by students. The study is intended to achieve similarities and discrepancies in the importance of the English-language achievement with general English and the implementation of digital storytelling. This study may be graded as an experimental investigation and classroom action research. This study employed cross-sectional research with independent speaking pre-test and post-test for experimental and control group design. Talking with storytelling therapy triggering different strategies is advised in experimental classes. It uses intervention research to change people's "talking," "doing" and "related practices". For the control group data combined with T-tests findings, a value of 0.417 has been achieved with an average value of -10.97436. In achieving speaking test outcomes, one may interpret that the treatment group has a more important meaning than the control group. The outcome of this study show that storytelling learning can help students at vocational health Level 2, more than the general English learning, achieve the high speaking achievement. Keywords: Promoting Storytelling, Speaking Achievement, Speaking Skill